2017
DOI: 10.17513/spno.26241
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Age and Sex Structure of the Population of Karachay-Cherkessia Republic

Abstract: Physics and Technology, Dolgoprudny, 5 Pirogov Russian National Research Medical University, Moscow, renazinchenko@mail.ru The paper considers addresses an age-sex structure of urban and rural populations of Karachay-Cherkess Republic and evaluated the load of hereditary diseases in three age cohorts of the population -pre-productive, reproductive and post-productive. Pre-productive population group is the smallest one and does not exceed one quarter in both urban and rural population. The most numerous group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Moreover, the proportion of child patients (of pre-productive age) varied from 38 to 51% in different surveyed populations (Zinchenko et al, 2019(Zinchenko et al, , 2020a. The proportion of patients in the reproductive age (18-45 years) out of the total number of patients with RHDs was 37.2% (from 31.91 to 40% by population); for the post-reproductive age (46 and older), only 17.5% (variation 17-22%) out of all patients (Elchinova et al, 2017). Analysis of the sample showed that some diseases do not occur in older age groups because they have high mortality in childhood and middle age (the rate is not constant and varies depending on the population, the causing gene, and the mutation).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the proportion of child patients (of pre-productive age) varied from 38 to 51% in different surveyed populations (Zinchenko et al, 2019(Zinchenko et al, , 2020a. The proportion of patients in the reproductive age (18-45 years) out of the total number of patients with RHDs was 37.2% (from 31.91 to 40% by population); for the post-reproductive age (46 and older), only 17.5% (variation 17-22%) out of all patients (Elchinova et al, 2017). Analysis of the sample showed that some diseases do not occur in older age groups because they have high mortality in childhood and middle age (the rate is not constant and varies depending on the population, the causing gene, and the mutation).…”
Section: Discussionmentioning
confidence: 98%
“…The Adyge-Khablsky district is multi-ethnic [12,28,29]. Sex ratio in the entire surveyed population: in pre-reproductive and reproductive groups-1:1 (M:F), in post-reproductive group-0.6:1 (M:F) [30].…”
Section: Survey Populationmentioning
confidence: 99%
“…The protocol consists of the population genetic and medical genetic sections and is intended for comprehensive population analysis based on the data on different genetic systems, including the genes of HDs, DNA polymorphisms, demographic data including surnames frequencies [30]. Each of the studied districts of the region has one central district hospital, which includes in-patient and out-patient facilities and several rural outpatient clinics and hospitals in the villages.…”
Section: Survey and Protocolmentioning
confidence: 99%